2020
DOI: 10.3390/en13071703
|View full text |Cite
|
Sign up to set email alerts
|

Economic Dispatch of Renewable Generators and BESS in DC Microgrids Using Second-Order Cone Optimization

Abstract: A convex mathematical model based on second-order cone programming (SOCP) for the optimal operation in direct current microgrids (DCMGs) with high-level penetration of renewable energies and battery energy storage systems (BESSs) is developed in this paper. The SOCP formulation allows converting the non-convex model of economic dispatch into a convex approach that guarantees the global optimum and has an easy implementation in specialized software, i.e., CVX. This conversion is accomplished by performing a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Este software es muy utilizado en la literatura especializada porque puede resolver problemas de optimización con múltiples variables. Algunos de los trabajos más relevantes usando este software han sido ubicación de generadores distribuidos en redes AC y DC usando variaciones de carga [18] y [19], despacho óptimo de baterías en redes AC y DC [20,21]…”
Section: Metodología De Soluciónunclassified
“…Este software es muy utilizado en la literatura especializada porque puede resolver problemas de optimización con múltiples variables. Algunos de los trabajos más relevantes usando este software han sido ubicación de generadores distribuidos en redes AC y DC usando variaciones de carga [18] y [19], despacho óptimo de baterías en redes AC y DC [20,21]…”
Section: Metodología De Soluciónunclassified
“…Power-flow analysis is an essential tool in the design and operation of alternating current (AC) and direct-current (DC) networks [1][2][3]. It employs loads that are typically modeled as constant power loads (CPLs), which generate hyperbolic non-convexities on the mathematical model that represents the power-flow problem (PF) in electrical grids [4,5].…”
Section: General Contextmentioning
confidence: 99%
“…The result of this consumer behaviour is a flatter load curve, which shows that even selfish actors can be beneficial to the system if the goal is congestion relief or peak shaving. Gil-González et al [91] showed that using an ESS in a distribution grid with high penetration of RES reduces its operating costs. Nazir et al [40] explored the possibility of using ESS for loss minimisation in unbalanced distribution grids with high penetration of PV.…”
Section: Distribution System-level Essmentioning
confidence: 99%